2007
DOI: 10.1007/s10585-007-9066-x
|View full text |Cite
|
Sign up to set email alerts
|

A novel study investigating the therapeutic outcome of patients with lytic, mixed and sclerotic bone metastases treated with combined radiotherapy and ibandronate

Abstract: Even though the therapeutic outcome for the three groups was similar, the degree of clinical response and reossification differed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 33 publications
6
30
0
Order By: Relevance
“…Mean bone density increasedby73%at10months.Similarresultswereobtained inasecondseriesof52patients [66],completepainresponse rates were > 76.4% at all assessments, opioid consumption wasmarkedlyreduced,andsignificantimprovementsinpain scores, QoL (QLQ-C30) and Karnofsky performance status (KPS)werereported.…”
Section: Effect Of Bisphosphonates On Bone Pain In Metastatic Breast supporting
confidence: 83%
“…Mean bone density increasedby73%at10months.Similarresultswereobtained inasecondseriesof52patients [66],completepainresponse rates were > 76.4% at all assessments, opioid consumption wasmarkedlyreduced,andsignificantimprovementsinpain scores, QoL (QLQ-C30) and Karnofsky performance status (KPS)werereported.…”
Section: Effect Of Bisphosphonates On Bone Pain In Metastatic Breast supporting
confidence: 83%
“…A phase 3 study in 470 patients with metastatic prostate cancer indicated that a single dose of local radiotherapy provided pain relief (combination of WHO pain ladder score and analgesic use) similar to a single dose of intravenous ibandronate [59]. In two small observational studies (N=70 and N=45), ibandronate combined with externalbeam radiotherapy in patients with bone metastases from solid tumors significantly decreased opioid use (P<0.001 in both studies) and improved pain scores relative to baseline [60,61]. However, despite these preliminary results, prospective randomized studies are needed to determine whether the combination of a bone-targeting agent with radiotherapy is more effective for pain relief than radiotherapy alone.…”
Section: Pain Outcomes Reported In Clinical Studies Of Radiotherapy Imentioning
confidence: 99%
“…It is best at evaluating bony structures with accuracy and can readily reveal reossification after successful treatment. 53,54 Reossification has been shown to occur in response to effective RT in several studies 8,21,[53][54][55] and to correlate with improvements in symptomatic pain scores. Peri-lesional fibrosis, such as lung fibrosis after thoracic SSRS, can also be easily identified on CT.…”
Section: Computed Tomographymentioning
confidence: 99%